1968
DOI: 10.1083/jcb.36.1.181
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Actinomycin D and Puromycin on the Acth-Induced Ultrastructural Transformation of Mitochondria of Cortical Cells of Rat Adrenals in Tissue Culture

Abstract: The ultrastructure of the mitochondria of the cultured cortical cells of rat adrenals was studied. In vivo it was found that the zona fasciculata mitochondria have vesicular internal structure. 600-A vesicles appear free in the matrix or as protrusions of the inner mitochondrial membrane. In tissue cultures of the fetal and newborn rat adrenal cortex it was seen that ACTH induces transformation of the tubulo-vesicular internal structure of the mitochondria to 600-A vesicles. Actinomycin D and puromycin inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

1969
1969
1979
1979

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(17 citation statements)
references
References 52 publications
1
15
0
1
Order By: Relevance
“…Abrupt withdrawal of the drug or administration of levallorphan reproduced the change in mitochondrial structure which appeared in case of a single injection of codeine, and corresponded to the fall in body wt.. this resembled that in Actinomycin D (1,6) or Amphenone B (7) treated rats and re administration of codeine to withdrawn rats resulted in a return to the pretreated structure. A satisfactory explanation for the differences between morphine and codeine in mor phological changes of intramitochondrial structure, however, cannot be given only from the results of this experiment.…”
Section: Discussionmentioning
confidence: 78%
“…Abrupt withdrawal of the drug or administration of levallorphan reproduced the change in mitochondrial structure which appeared in case of a single injection of codeine, and corresponded to the fall in body wt.. this resembled that in Actinomycin D (1,6) or Amphenone B (7) treated rats and re administration of codeine to withdrawn rats resulted in a return to the pretreated structure. A satisfactory explanation for the differences between morphine and codeine in mor phological changes of intramitochondrial structure, however, cannot be given only from the results of this experiment.…”
Section: Discussionmentioning
confidence: 78%
“…Later, Sabatini et al, (1962) reported that mitochondria of fasciculata cells in hypophysectomized rat were provided with the straight tubular cristae as similar to those of zona glomerulosa cells, and these cristae were transformed to the vesicular type after ACTH administration. The findings of Kahri (1968) that tubular cristae of cultured adrenocortical cells were reverted to vesicular type under the added ACTH in vitro. He indicated that the mitochondrial cristae is under the control of ACTH, and may be related to the conversion into the original cell function.…”
Section: Discussionmentioning
confidence: 97%
“…A tissue culture method suitable for long-term cultivation [Kauri, 1966] was used. The medium consisted of 50% Melnick's solution A (Hanks' balanced salt solution -[-0.5 % lactalbumin hydrolysate); 25% calf serum (ultrafiltrated 4-heat inactivated 30 min at 56 °C); 25 % amino acid Parker (Pharmaceutical Manufactures, Orion Oy, Finland).…”
Section: Methodsmentioning
confidence: 99%
“…Several in vitro studies [Kauri, 1966[Kauri, , 1968b have shown that in the rat adrenal cortex, ACTH plays the main role in the differentiation of zona fasciculata and reticularis cells from poorly differentiated zona glomerulosa -zona inter media cells. Several hypotheses have been offered to explain the differences in functional activity of the fetal zone cells of the human embryo and zona fasciculata of the adult cortex, and even more speculative opinions exist on the mechanism which controls the functional activity and morphological differentiation of the fetal zone cells of the adrenal cortex in humans.…”
Section: Introductionmentioning
confidence: 99%